2017
DOI: 10.1016/j.envint.2017.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Metals, hormones and sexual maturation in Flemish adolescents in three cross-sectional studies (2002–2015)

Abstract: Sex hormone levels and timing of sexual maturation are considered important markers for health status of adolescents in puberty, and previous research suggests they might be influenced by metal exposure. In three campaigns of the Flemish Environment and Health Study (FLEHS I 2002-2006; FLEHS II 2007-2011 and FLEHS III 2012-2015), data were collected on internal exposure to metals (Cd, Cu, Pb, Cr, Mn, Tl, Ni, Sb, Hg, As and As species) and sexual maturation in 2671 14-15years old adolescents. All metals were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…The mean E Cd /C cr in men was almost identical to that of women (Table 1). It is increasingly recognized that creatinine adjustment is problematic, and urine specific gravity has been used to correct for dilution effects [9,44,45,[50][51][52]. Herein, we have demonstrated the utility of normalizing excretion rate of metals to creatinine clearance that only required simultaneous urine and blood sampling together with the equations, given in Section 2.3 [33,35].…”
Section: Discussionmentioning
confidence: 98%
“…The mean E Cd /C cr in men was almost identical to that of women (Table 1). It is increasingly recognized that creatinine adjustment is problematic, and urine specific gravity has been used to correct for dilution effects [9,44,45,[50][51][52]. Herein, we have demonstrated the utility of normalizing excretion rate of metals to creatinine clearance that only required simultaneous urine and blood sampling together with the equations, given in Section 2.3 [33,35].…”
Section: Discussionmentioning
confidence: 98%
“…Metals such as lead interact heavily with calcium in the body [77], and a recent study looking at metal interactions via calcium pathways showed broader differences in body stores of metals in children during puberty [78]. Several metals, including lead, cadmium, arsenic, thallium, and copper, can also affect levels of free testosterone and estradiol [7981], Differential levels of sex hormones also result in sex-specific variation in development of the brain. Studies have reported sex differences in prenatal testosterone levels and later development of behavioral disorders [82].…”
Section: Discussionmentioning
confidence: 99%
“…Cadmium has also been shown to interact with sex hormones and cause an increase in testosterone production in women [81]. Another study showed that several metals, including cadmium, arsenic, thallium, and copper, have an impact on sexual maturation and hormone levels [79]. Additionally, lead is well known to affect hormone levels of free testosterone and estradiol [79, 80].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the framework of GOLIATH, we will explore epidemiologic associations in the "Flemish Environment and Health Studies" that have been running since 2002 (FLEHS, http://www.milieuen-gezondheid.be/) [95][96][97][98][99][100][101][102] and in the "Prevention and Incidence of Asthma and Mite Allergy" cohort study (PIAMA, https://piama.iras.uu.nl/english/) that has been running since 1996 [103,104]. Both cohort studies contain a detailed characterization of lifestyle and environmental exposures as well as information on metabolically relevant molecular and physical outcome parameters at multiple ages in childhood and adolescence.…”
Section: Epidemiological Studiesmentioning
confidence: 99%